Development and delivery of an e-learning course “Calculation Methods for Power Systems Stability" in learning management system; 11th International Technology, Education and Development Conference (INTED2017), 6-8 March, 2017, Valencia, Spain - Khrushchev Yu. V. Yuri Vasilievich; Batseva N. L. Natalya Lenmirovna; Fix N. P. Natalia Pavlovna; Shaidullina A. R. Albina Rafisovna; Kolesnikov S. V. Stanislav Vyacheslavovich (2017, 2017)
Title screen